Invisible, solidary, unbranded and passionate: everyday life as a freelance and precarious worker in four Italian radio stations. (1st December 2016) - Tiziano Bonini; Alessandro Gandini
Abstract : This article presents an investigation into the everyday lives of freelance radio producers in the Italian radio industry from a perspective that applies the sociology of work to the study of media production. The study adopted an ethnographic approach to explore working conditions and experiences of insecurity, uncertainty, socialising, networking and isolation. The authors identified four features of the radio producers' work, which go well beyond the fact that passion functions as a cover for unfair working conditions. The work of these radio producers is invisible, passionate, unbranded and solidaristic. These features interconnect with the conventional ethos of freelance and precarious workers in the creative industries, where professional identity becomes subsumed by the dominant logic of the industry. If we adopt a Marxist perspective, we could argue that this freelance 'reserve army' experiences a specific kind of 'subsumption' with roots in the workers' teenage fandom-based milieux and in broader popular culture.